2011
DOI: 10.1111/j.1600-6143.2011.03686.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review: Kidney Transplantation Compared With Dialysis in Clinically Relevant Outcomes

Abstract: Individual studies indicate that kidney transplantation is associated with lower mortality and improved quality of life compared with chronic dialysis treatment. We did a systematic review to summarize the benefits of transplantation, aiming to identify characteristics associated with especially large or small relative benefit. Results were not pooled because of expected diversity inherent to observational studies. Risk of bias was assessed using the Downs and Black checklist and items related to time-to-event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
826
3
44

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,174 publications
(880 citation statements)
references
References 105 publications
7
826
3
44
Order By: Relevance
“…(9) This results indicated that patients undergone renal transplantation had improvements in all dimensions of quality of life improvement evaluated by WHOQOL-BREF compared to before transplantation as confirmed by other studies. (3,8,25) This study contributes to the research literature on QoL chronic renal diseases patients submitted to kidney transplantation. Recent research that examined the influence of health-related QoL issues in patients undergoing renal transplantation reported that QoL scores were able to predict mortality and graft failure independently of sociodemographic and clinical risk factors of the patients, therefore, indicating the importance of QoL evaluation in this group of patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(9) This results indicated that patients undergone renal transplantation had improvements in all dimensions of quality of life improvement evaluated by WHOQOL-BREF compared to before transplantation as confirmed by other studies. (3,8,25) This study contributes to the research literature on QoL chronic renal diseases patients submitted to kidney transplantation. Recent research that examined the influence of health-related QoL issues in patients undergoing renal transplantation reported that QoL scores were able to predict mortality and graft failure independently of sociodemographic and clinical risk factors of the patients, therefore, indicating the importance of QoL evaluation in this group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…While waiting for a donor, the chronic renal disease patients have other forms of Renal Replacement Therapy (RRT) allow the maintenance of their life and also justify the increasing number of patients registered on the waiting list for a kidney transplantation. (3,4) Renal Insufficiency (RI) and the complexity of their treatment constitute a serious public health problem worldwide, with social and financial burden resulting from increasing rates of young patients with renal function failure. (6) Thus, measurement of patients' Quality of Life (QoL) after kidney transplantation, is a relevant topic for many individuals who are on dialysis in Brazil and receive care in one of the 696 dialysis centers registered in the Nephrology Brazilian Society (NBS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…O transplante renal é considerado o melhor tratamento da doença renal crônica (DRC) [1,2]. Essa terapêutica associa-se à diminuição do risco de mortalidade, além de melhorar a qualidade de vida e proporcionar o fim das restrições alimentares [3,4].…”
Section: Introductionunclassified
“…Increasing prevalence of ESRD on one hand, and stagnant or declined organ donation on the other hand prolong waiting time for kidney transplantation. Thus, the age of potential transplant recipients and comorbidities of patients as a result of dialysis treatment seem to be increasing over time [4]. Many factors have impact on the function of transplanted kidney.…”
Section: Introductionmentioning
confidence: 99%